2013
DOI: 10.1111/jvim.12247
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Immune‐Complex Glomerulonephritides in Dogs Biopsied for Suspected Glomerular Disease: 501 Cases (2007–2012)

Abstract: Background Glomerulonephropathies are common causes of kidney disease in dogs. Objective To determine the prevalence of immune‐complex glomerulonephritis (ICGN) in North American dogs biopsied for suspected glomerular disease. Animals Renal biopsies (n = 733) submitted to the Texas Veterinary Renal Pathology Service between January 1, 2007 and December 31, 2012 were reviewed. Dogs were included if the biopsy was performed for suspected glomerular disease. Methods Specimens were evaluated by light microscopy (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
73
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(82 citation statements)
references
References 24 publications
6
73
1
2
Order By: Relevance
“…Cases with an active sediment were excluded from analysis. Renal biopsies were routinely processed for light (LM) and transmission electron microscopy (TEM) as previously described 24. Criteria for diagnosis of renal disease included persistent proteinuria, azotemia, or both.…”
Section: Methodsmentioning
confidence: 99%
“…Cases with an active sediment were excluded from analysis. Renal biopsies were routinely processed for light (LM) and transmission electron microscopy (TEM) as previously described 24. Criteria for diagnosis of renal disease included persistent proteinuria, azotemia, or both.…”
Section: Methodsmentioning
confidence: 99%
“…63 The role of estrogens is intriguing because proteinuric dogs diagnosed with FSGS were disproportionately female (74 of 103, 71.8%), almost all of which (93%) were spayed. 72 In aged Fisher 344 rats, the pattern of glomerular gene expression resembles changes observed in arteries with arteriosclerosis. Specifically, there is transcriptional regulation of cell adhesion molecules, chemotactic factors, oxidoreductases (specifically ceruloplasmin), MMPs, coagulation factors, and TGF-ß.…”
Section: Molecular Mechanisms Of Renal Agingmentioning
confidence: 99%
“…The WSAVA-RSSG defines FSGS as sclerosis that effaces <50% of a glomerular tuft and involves <50% of glomeruli of the sample. 13 Given that FSGS is associated with proteinuria in humans 22 and dogs, 72 its presence might indicate clinically relevant disease. Notably, FSGS was observed (but not quantified) in the 2 of the canine studies discussed above 29,57 ; however, either it was not mentioned, 11,74 or it was reported as being absent in the others.…”
Section: Glomerular Lesionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nearly 60% of dogs with glomerular proteinuria will have either immune-complex mediated glomerulonephritis or amyloidosis (Schneider et al, 2013), both of which may represent an aberrant or excessive immune or inflammatory response to an infectious, neoplastic or inflammatory condition. Cats rarely get glomerulonephritis but a percentage of these cats would also be expected to have developed this secondary to a systemic disease.…”
Section: Renal Biopsymentioning
confidence: 99%